Os desafios do gerenciamento do brand equity no ponto de venda - Germano, Aline Vilanova (2011)
Over the past decades, consumers and consumer goods suppliers have been more and more under the influence of the environment where the purchase decision takes place, the store. On the other hand, brands are considered, nowadays, one of the most important and valuable assets one institution can have. Through a solid and established brand, it is possible to attribute unique associations to products, reducing the focus on the price, in the shopping decision moment, as well as being a way to facilitate consumers choice. This work has the general objective of studying the influence of the marketing activities in the point of sales for building and positioning brands, discussing if managers work these activities focusing on maximizing the brand value, building and managing its brand equity. The study has been done through a exploratory research and empirical verification, which evaluation instruments were applied in a brand manager from the category studied and in consumers who shop in drugstores. The results obtained with the research showed that the point of sales has a function of impact in the brand management work. Even though its commercial aspect and short term, brand managers need to consider point of sales activities as a strategic element in the value generation and brand equity managing process of a brand. So, given its relevance, it is important managers ongoing evaluation about the point of sales activities their brands perform, in order to verify if they are in accordance to the brand positioning and relationship desired to be established with consumers